Seismic assessment of a typical masonry residential building in Bosnia and Herzegovina - Ademović, Naida (2012)
The paper elaborates the seismic behaviour of a typical masonry building in B&H built in the 60’s without any seismic guidelines. Numerical modelling has been done in two different software packages, namely DIANA and 3MURI. In both approaches, adequate constitutive assumptions were assumed to take into account the nonlinear behaviour of masonry. Seismic vulnerability has been conducted by performing pushover and time history analyses. A comparison in terms of dynamic properties, crack pattern and capacity curves was done and a good agreement has been found between the two software packages. The paper's aim was to assess the seismic safety of this type of construction. A further objective was to investigate if simple software packages could be used for the assessment of these buildings. As a wide stock of this type of buildings is located through the former territory of ex-Yugoslavia, this work would enable a better understanding of this type of structures and quick overview of their actual seismic behavior.